2012
DOI: 10.1111/j.1423-0410.2012.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

International reference reagents to standardise blood group genotyping: evaluation of candidate preparations in an international collaborative study

Abstract: The establishment of RBC1, RBC4, RBC5 and RBC12 as World Health Organization Reference Reagents will facilitate international standardisation of blood group genotyping and ensure that such tests are sufficiently sensitive and specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This study revealed that genotyping using a microarray platform is a feasible blood group antigen genotyping tool that produces reliable data. The concordance rate with bidirectional sequencing was 100% and with serologic testing was 98·56%; these findings were in agreement with previous literature showing a 1% discrepancy rate, which could be attributed to the high rate of false‐positive results in serologic testing (Denomme & Oene, ; Kappler‐Gratias et al ., ; Bolye et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This study revealed that genotyping using a microarray platform is a feasible blood group antigen genotyping tool that produces reliable data. The concordance rate with bidirectional sequencing was 100% and with serologic testing was 98·56%; these findings were in agreement with previous literature showing a 1% discrepancy rate, which could be attributed to the high rate of false‐positive results in serologic testing (Denomme & Oene, ; Kappler‐Gratias et al ., ; Bolye et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the preferred source of reference DNA is B‐lymphoblastoid cell lines, which should be established for all common alleles, while we may have to be content with homogeneous synthetic controls for many of the less common alleles. Use of reference reagents as quality control material, currently developed by the FDA (see Web resources) and ISBT, will be widely applied in the future. Similar to monoclonal antibodies, such reagents are easily available and, once established, pose no consent issues.…”
Section: Discussionmentioning
confidence: 99%
“…The panel includes four DNA samples covering the most clinically important homozygous and heterozygous genotypes within RH, FY, KEL, JK, DO, and MNS blood group systems ( Table 4). The material was validated in an international collaborative study by PCR-ASP or PCR-SSP, PCR-RFLP, Multiplex SSP assays, real-time PCR, Immucor Beadchip array, Progenika BLOODchip array, Luminex array, and 5′ Nuclease assay [98].…”
Section: Molecular Testing: Standards For Rbc Antigensmentioning
confidence: 99%